The Influence of Physical Activity, Knowledge, and Diet on The Incidence of Degenerative Diseases in The Gymnastics Community - Budhi Setianto (Journal of Health Sciences, 2024)
According to statistics from the 2018 Basic Health Research, 65.7% of Indonesians suffer from degenerative illnesses, such as diabetes, high blood pressure, stroke, and joint disease. According to Ministry of Health data, the number of persons with diabetes would have increased to 6.2% (10.8 million) by 2020, and 236,710 diabetes-related fatalities were recorded in 2021. Data on risk variables and outcomes were gathered concurrently in this cross-sectional research, which uses a descriptive quantitative approach. Data for the research was gathered using Google Forms, and the study population consists of 62 senior citizens from RW 07, Wonokromo Village. The incidence of degenerative illnesses is the dependent variable, while physical activity, knowledge, food, and lifestyle are the independent factors. The Chi-Square test and cross-tabulation were used for analysis. The findings indicate that, albeit just once a week, most respondents participate in physical activities like gymnastics largely for their physical well-being. Most respondents stick to a set eating schedule even when they do not strictly follow a diet. The results suggest that although education, nutrition, and lifestyle do have a major impact on the occurrence of degenerative diseases, physical exercise alone does not.